A parameter reduced adaptive quasi-linear viscoelastic model for soft biological tissue in uniaxial tension. (February 2022) - Aryeetey, Othniel J.; Frank, Martin; Lorenz, Andrea; Estermann, Sarah-Jane; Reisinger, Andreas G.; Pahr, Dieter H.
Abstract: Mechanical characterisation of soft viscous materials is essential for many applications including aerospace industries, material models for surgical simulation, and tissue mimicking materials for anatomical models. Constitutive material models are, therefore, necessary to describe soft biological tissues in physiologically relevant strain ranges. Hereby, the adaptive quasi-linear viscoelastic (AQLV) model enables accurate modelling of the strain-dependent non-linear viscoelastic behaviour of soft tissues with a high flexibility. However, the higher flexibility produces a large number of model parameters. In this study, porcine muscle and liver tissue samples were modelled in the framework of the originally published AQLV (3-layers of Maxwell elements) model using four incremental ramp-hold experiments in uniaxial tension. AQLV model parameters were reduced by decreasing model layers ( M ) as well as the number of experimental ramp-hold steps ( N ). Leave One out cross validation tests show that the original AQLV model (3 M 4 N ) with 19 parameters, accurately describes porcine muscle tissue with an average R 2 of 0.90 and porcine liver tissue, R 2 of 0.86. Reducing the number of layers ( N ) in the model produced acceptable model fits for 1-layer ( R 2 of 0.83) and 2-layer models ( R 2 of 0.89) for porcine muscle tissue and 1-layer ( R 2 of 0.84) and 2-layer model ( R 2 of 0.85) for porcine liver tissue. Additionally, a 2 step (2 N ) ramp-hold experiment was performed on additional samples of porcine muscle tissue only to further reduce model parameters. Calibrated spring constant values for 2 N ramp-hold tests parameters k 1 and k 2 had a 16.8% and 38.0% deviation from those calibrated for a 4 step (4 N ) ramp hold experiment. This enables further reduction of material parameters by means of step reduction, effectively reducing the number of parameters required to calibrate the AQLV model from 19 for a 3 M 4 N model to 8 for a 2 M 2 N model, with the added advantage of reducing the time per experiment by 50%. This study proposes a 'reduced-parameter' AQLV model (2 M 2 N ) for the modelling of soft biological tissues at finite strain ranges. Sequentially, the comparison of model parameters of soft tissues is easier and the experimental burden is reduced. Graphical abstract: Image 1 Highlights: Soft biological tissues require non-linear viscoelastic models. AQLV models porcine muscle and liver tissue accurately. Flexibility of AQLV enables reduction of model parameters (from 19 to 8). Parameter reduced models ease material comparison and lower experimental burden.